2019
DOI: 10.1111/ejn.14631
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota–brain axis in depression: The role of neuroinflammation

Abstract: Major depressive disorder (MDD) is a psychiatric condition that affects a large number of people in the world, and the treatment existents do not work for all individuals affected. Thus, it is believed that other systems or pathways which regulate brain networks involved in mood regulation and cognition are associated with MDD pathogenesis. Studies in humans and animal models have been shown that in MDD there are increased levels of inflammatory mediators, including cytokines and chemokines in both periphery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 152 publications
1
107
0
9
Order By: Relevance
“…The pathophysiology of depression is multifactorial. Studies in recent decade has pointed out that stress-induced changes in the gut microbiota would lead to a systemic inflammation which in different ways would modulate brain inflammatory pathways and cause depression [140]. Some preclinical studies had demonstrated that probiotics, which have potential antidepressant properties, can attenuate stress-inducing IL-6 [141,142].…”
Section: How To Reduce Il-6 Activity Through Gut Microbiota Modulation?mentioning
confidence: 99%
“…The pathophysiology of depression is multifactorial. Studies in recent decade has pointed out that stress-induced changes in the gut microbiota would lead to a systemic inflammation which in different ways would modulate brain inflammatory pathways and cause depression [140]. Some preclinical studies had demonstrated that probiotics, which have potential antidepressant properties, can attenuate stress-inducing IL-6 [141,142].…”
Section: How To Reduce Il-6 Activity Through Gut Microbiota Modulation?mentioning
confidence: 99%
“…The microbiota in the gut and the brain can communicate through a variety of routes that involve neuroendocrine, neuroimmune, and autonomic nervous systems pathways (Grenham et al, 2011;Mayer, 2011). The immune system is particularly important (Carlessi et al, 2019) where cytokines components of the immune system communicate directly with the brain via the vagal nerve inducing changes in the BBB (Quan, 2008). It also affects the hypothalamic pituitary adrenal (HPA) axis, that centralizes the stress response system, stimulated by physical or psychological situations (Scriven et al, 2018).…”
Section: The Microbiota-gut-brain Axismentioning
confidence: 99%
“…Informações encontradas em um dos artigos escolhidos como foco dessa revisão demonstram que a ingestão do padrão alimentar característico das dietas ocidentais de forma crônica, pode causar prejuízos ao metabolismo, principalmente se aliado ao estilo de vida sedentário. A inatividade e o alto consumo energético, podem gerar acúmulo de gordura, ganho de peso, inflamação sistêmica por meio de mecanismos relacionados a adiposidade, como ativação do gene NLRP3 (WONG et al, 2016), disbiose na microbiota intestinal por meio da produção de citocinas inflamatórias, que são liberadas quando há absorção em excesso de gorduras e substâncias estranhas ao intestino, o que gera ativação do sistema imune por vias inflamatórias que se estende por todo o organismo (CARLESSI et al, 2019).…”
Section: Dietas Ocidentais E Sua Relação Com Depressãounclassified
“…A presença dessas células imunes no cérebro pode levar a um aumento na concentração de quinurenina, metabólito que ao entrar no cérebro promove estresse celular, e consequentemente gera uma redução na produção de serotonina no órgão, o que discutiremos abaixo mais especificamente (LI et al, 2017). Sendo assim, todo esse processo é nomeado como neuroinflamação e quando crônico pode levar a neurodegeneração, de acordo com (CARLESSI et al, 2019; WESTFALL e PASINETTI, 2018), um dos artigos escolhidos para embasamento deste estudo.…”
Section: Inflamação Intestinal E Ativação Do Sistema Imuneunclassified
See 1 more Smart Citation